Distinct histone modifications define initiation and repair of meiotic recombination in the mouse - Buard, Jérôme; Barthès, Pauline; Grey, Corinne; de Massy, Bernard (The EMBO journal, 2009)
Little is known about the factors determining the location and activity of the rapidly evolving meiotic crossover hotspots that shape genome diversity. Here, we show that several histone modifications are enriched at the active mouse Psmb9 hotspot, and we distinguish those marks that precede from those that follow hotspot recombinational activity. H3K4Me3, H3K4Me2 and H3K9Ac are specifically enriched in the chromatids that carry an active initiation site, and in the absence of DNA double‐strand breaks (DSBs) in Spo11 −/− mice. We thus propose that these marks are part of the substrate for recombination initiation at the Psmb9 hotspot. In contrast, hyperacetylation of H4 is increased as a consequence of DSB formation, as shown by its dependency on Spo11 and by the enrichment detected on both recombining chromatids. In addition, the comparison with another hotspot, Hlx1 , strongly suggests that H3K4Me3 and H4 hyperacetylation are common features of DSB formation and repair, respectively. Altogether, the chromatin signatures of the Psmb9 and Hlx1 hotspots provide a basis for understanding the distribution of meiotic recombination.